Impact of response to treatment in health-related quality of life patient-reported outcomes in elderly patients with relapsed multiple myeloma. Issue 1 (2nd January 2021) - Oriol, Albert; Ibarra, Gladys; Abella, Eugènia; Motlló, Cristina; Cibeira, Maria-Teresa; Garcia, Antoni; Escoda, Lourdes; Granell, Miquel; Ben-Azaiz, Randa; Cervera, Marta; Cabezudo, Elena; Fernandez, Carlos; et al.
Abstract: Multiple myeloma (MM) is a recurrent malignancy with a high impact on quality of life. Improved survival relies on the combination of drugs and extended duration of therapy, raising concerns on its toxicity burden in elderly patients. Health-related quality of life measurements attent to capture health aspects relevant to patients other than efficacy. This prospective study aimed to understand the relationship between MM-related symptomatology and other quality of life dimensions using the EORTC QLQ-MY20 questionnaire in individuals with relapsed or refractory MM. Irrespective of treatment modality, over 50% of patients who responded to treatment had significant omprovements of reported scores in all domains. Conversely, disease progression was associated with score deterioration not only in the MM-related symptoms domain but also in all other domains. HRQoL adds valuable information to the established efficacy endpoints but an adequate interpretation of HRQoL outcomes in randomized trials should require stratification according to response.